Online management systems for primary school students. - Zeki, Akram M.; Mustakim, Farah Nadiah (IIUM Press, 2011)
The aim of this study is to develop a student's management system for primary schools, to provide Web-based Intelligence system for the primary school, and to offer convenience to the school's management in organizing the student's information and details. The system should be reliable to key in the student's information and must be fast and save time using semiautomated system instead of using manual form. In the case of unexpected consequences, the system should have a backup to keep all the files properly and to make the management easily monitor the students of the school. The objective of this project is to develop a system that can monitor each student of a specific primary school so that the school can know which student needs help in their studies or other aspects for improvement and which student are doing well. The system aims to provide the systematic ways of recording the information in order to decrease the problem of loose monitoring of student's information.